ORIENTASI MAHASISWA SOSIOLOGI DALAM PEMILIHAN LAPANGAN PEKERJAAN - Yunita Clara Br Simbolon; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted at the University Riau Social Sciences Study Program Sociology. The purpose of this study was determine the orientation of Sociology students and business forms in achieving their orientation. The technique of determining the Proportionate Stratified Random Sampling and setting a sample of 83 respondents. The author uses descriptive quantitative methodes and data intruments or questionnaire and documentation. Based on the results of the study showed that the orientation of Sosiology students in choosing the most desirable jobs is the State Civil Apparatus (SCA ) with a total of 37 respondents or 44,6%, the amount of this data indicates that being an SCA is desire of most respondents. The second interest is entrepreneurship wit a tota of 20 respondents or 24,1%, the reason some respondents choose entrepreneurship is that they want to continue a family bussiness, not bound, and can open new jobs. The third most popular jobs are in the field of State Owned Enterprises with 17 respondents or 20,5%, while the reasons are due to the existence of a guaranteed company survival, clear career paths, ang high salaries although they are still fresh graduates. The most desirable jobs are the Private Sector Owned Enterprices wit 17 respondents or 10,8%. Form of business in achieving orientation in the selection of employment consists of seeking employment information through, continuing education, actively participating in training, building networks, actively participating in organizations, actively participating in socialzation, ang continuing family business. The most dominant form of business is to build a network, and the least is to continue a family business.